Endovascular treatment of tandem vascular occlusions in acute ischemic stroke. (27th February 2014) - Puri, Ajit S; Kühn, Anna L; Kwon, Hyon-Jo; Khan, Muhib; Hou, Samuel Y; Lin, Eugene; Chueh, Juyu; van der Bom, Imramsjah MJ; Dabus, Guilherme; Linfante, Italo; Gounis, Matthew J; Wakhloo, Ajay K
Abstract : Background and purpose: Tandem vascular occlusions are an important cause of acute ischemic stroke (AIS) and present unique treatment challenges. We report our experience of managing a subset of AIS patients with extracranial vascular stenting/angioplasty and intracranial revascularization. Methods: Consecutive patients who presented at three centers with AIS from tandem vascular occlusions confirmed by brain and neck CT imaging were included in the study. We retrospectively analyzed the patient demographics, National Institute of Health Stroke Scale (NIHSS) score and modified Rankin Scale (mRS) score at the time of admission, treatment strategy, angiographic results using the Thrombolysis In Cerebral Infarction (TICI) score, and clinical and imaging follow-up. Results: Twenty-eight patients were included. The mean NIHSS score at admission was 18. Extracranial carotid occlusions with a concomitant middle cerebral artery occlusion were seen in 89.3% of patients (n=25) and vertebral artery combined with basilar artery lesions in 10.7% (n=3). An antegrade approach (ie, treatment of the extracranial lesion first) was used in 24 patients (85.7%). Proximal occlusion recanalization was achieved usually with a stent (n=27; 96.4%). Pursuant to intracranial revascularization techniques, ≥TICI 2A recanalization was seen in 96.4% of patients. An mRS score of ≤2 at 90 days was achieved in 56.5% of patients. Conclusions: Our study shows preliminary data from three centers on recanalization of tandem occlusions in patients presenting with AIS. There was a preference to revascularize the proximal occlusion using a stent followed by distal recanalization with mechanical thrombectomy, intra-arterial thrombolysis or a combination of these. This approach has low periprocedural complications and can achieve an excellent angiographic and clinical outcome.